2020
DOI: 10.1088/1361-6528/ab62ca
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism underlying silicon oxide based resistive random-access memory (ReRAM)

Abstract: In this work, we have inspected the theoretical resistive switching properties of two ReRAM models based on heterojunction structures of Cu/SiO x nanoparticles (NPs)/Si and Si/SiO x NPs/Si, in which dielectric layers of the silica nanoparticles present dislocations at bicrystal interfaces. To validate the theoretical model, a charge storage device with the structure Cu/SiO x /Si was fabricated and its ReRAM properties were studied. Our examinations on the electrical, thermal and structural aspects of resistive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…It is well known that the room temperature thin films present a nanoporous configuration and consist of small and randomly distributed small grains [21,22]. As a result, Cu or Ag ions can easily move along these piled grains, under the application of external voltage bias, and reach the bottom electrode (BE) [23]. In addition, the presence of abundant oxygen with the SiO 2 matrix facilitates the partial oxidation of the active electrode that is also accelerated by the presence of moisture at the anode surface [24].…”
Section: Experimental Characteristicsmentioning
confidence: 99%
“…It is well known that the room temperature thin films present a nanoporous configuration and consist of small and randomly distributed small grains [21,22]. As a result, Cu or Ag ions can easily move along these piled grains, under the application of external voltage bias, and reach the bottom electrode (BE) [23]. In addition, the presence of abundant oxygen with the SiO 2 matrix facilitates the partial oxidation of the active electrode that is also accelerated by the presence of moisture at the anode surface [24].…”
Section: Experimental Characteristicsmentioning
confidence: 99%
“…There are many metal-oxide film-fabrication methods: atomic layer deposition (ALD) [ 58 , 59 ], the sol-gel method [ 60 ], magnetron sputtering [ 61 , 62 ], and pulsed laser deposition (PLD) [ 63 ]. Forming-free nanocrystalline ZnO films grown using PLD have been shown to exhibit improved resistive switching characteristics, with higher R HRS / R LRS ratios and lower operating voltages [ 64 , 65 , 66 , 67 ]. PLD is a relatively inexpensive technology for growing thin films that meets the requirements for fabricating memristive devices, primarily because of the possibility of precise adjustment of the electrophysical parameters of the oxide by varying the growth parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Although different transitional metal oxides are used as switching material (SM) of RRAM devices such as TaOx [3,4], HfOx [5,6], TiOx [7], etc. but the reports with SiOx is less [8][9][10]. Previously some reports [11][12][13] showed that thickness enhancement can cause several performance degradations such as increase in set voltage hence power consumption enhancement [11], or decrease in high resistance state (HRS) and switching uniformity [12], or abrupt switching, degraded HRS and poor reliability [13] are some key effects of thickness enhancement.…”
Section: Introductionmentioning
confidence: 99%